An axiomatization of the Euclidean compromise solution - Mark Voorneveld; Anne van den Nouweland; Rich McLean (Stockholm School of Economics, The Economic Research Institute (EFI), 2008)
The utopia point of a multicriteria optimization problem is the vector that specifies for each criterion the most favourable among the feasible values. The Euclidean compromise solution in multicriteria optimization is a solution concept that assigns to a feasible set the alternative with minimal Euclidean distance to the utopia point. The purpose of this paper is to provide a characterization of the Euclidean compromise solution. Consistency plays a crucial role in our approach.
Keywords: C60; C61; 330; Consistency; Euclidean compromise solution; Multicriteria optimization; Mathematische Optimierung; Multikriteria-Verfahren; Theorie